Penentuan Pemberian Bantuan Smart Fishing Kepada Nelayan Menggunakan Metode SMART - Nuris, Nisa Dienwati (Jurnal ICT : Information Communication & Technology, 2021)
Abstract- Fisheries development as part of national economic development has the aim, among others, to improve the standard of living and welfare of the fishing community. The effort to realize the Champion fisherman and Fish Warehouse program to encourage fish production in the West Java provincial government of West Jawa through the Department of Marine Affairs and Fisheries seeks to develop fishery potential through the SMART FISHING assistance program. So that the aid program is properly, an application is made to determine the fisherman who are entitled to receive assistance. The purpose of this study is producing a SAFIA application using the SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE method based on a web framework that can facilitate the Department of Marine Affairs and Fisheries of West Java to determine the best group of fisherman according to the criteria for receiving assistance. The Result of making this research is how the SAFIA application works with accuracy